-56=c-(-8)

Simple and best practice solution for -56=c-(-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -56=c-(-8) equation:


Simplifying
-56 = c + -1(-8)

Multiply -1 * -8
-56 = c + 8

Reorder the terms:
-56 = 8 + c

Solving
-56 = 8 + c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
-56 + -1c = 8 + c + -1c

Combine like terms: c + -1c = 0
-56 + -1c = 8 + 0
-56 + -1c = 8

Add '56' to each side of the equation.
-56 + 56 + -1c = 8 + 56

Combine like terms: -56 + 56 = 0
0 + -1c = 8 + 56
-1c = 8 + 56

Combine like terms: 8 + 56 = 64
-1c = 64

Divide each side by '-1'.
c = -64

Simplifying
c = -64

 

See similar equations:

| 8x+3=50 | | t+12=-18 | | 8x+3=59 | | -6.7=y-27 | | x+x+x-2=61 | | 2x+2=2x-4 | | 5X-2X=2X+33 | | -27+x=x+11 | | 12.4-k=4.3 | | 3(x+2)=3 | | x^2-2x-63= | | 6X-340=4X+120 | | 5x-34=15 | | 10x-4=8x+2 | | 5x+3-3(x-2)=-84 | | 5.77=q+9 | | x-289=162 | | 10X-81=X+9 | | 2x-7=7x+3 | | -11=2(x+4)-(x+3) | | 3x=-3 | | 4(p+1)=2p-2 | | X+7=-3X+28 | | 2(k+1)=5(k-2) | | 4x^2+7=9x | | x+x+x-9=37 | | 2X-10=-3X+40 | | 5b-4=2b+5 | | x-260=-30 | | 2y-2=4y+2 | | x-260=-130 | | 12X-144=9X+9 | | M+3m=72-5m | | 7x+10x=85 | | 6x=3x+6 | | (2b-14)(14b-2)=0 | | w-(43.7)=-4.342 | | 17X-186=3X+10 | | 9=-2x+15 | | Y-5=2y+10 | | -3282=n+1111 | | -3.1=4.75-e | | -7b=-77 | | 3X-7=2X+5 | | (x^4-2x^8)=0 | | -144=12b | | -15m=15 | | 36=-6t | | 7X+8=4X-10 | | -2.1=-.7c | | 4x+35=8x+2 | | 4m=-2 | | .24t=1.2 | | -.0003=.02c | | -12n=-56 | | 23.66=13r | | 33k=-878 | | 24-32x=(-4)-(-6x) | | 9x-4=23 | | 3x^2+8=16 | | 8(5-6)+4.6=-22 | | 8(s-6)+4.6=-22 | | 4+5x=40+x | | 2n+3n-7=-41 | | 4x^2+16x+24=0 |